1978
DOI: 10.1007/bf02533857
|View full text |Cite
|
Sign up to set email alerts
|

Bile acids in tissues: Binding of lithocholic acid to protein

Abstract: Human liver contains two forms of lithocholic acid. One form is readily extractable by 95% ethanol/0.1% ammonia (soluble lithocholate, SL), while the other remains firmly bound to the residue (tissue-bound lithocholate, TBL). TBL could be hydrolytically released using clostridial cholanoylamino acid hydrolase, suggesting a peptide link between lithocholate and protein. With bovine serum albumin (BSA), lithocholic acid showed spontaneous amino group-modifying activity. When small molecular weight lysine (alpha-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Low doses of primary bile acids increase the number of aberrant crypt foci in the colon (29); conversely, higher concentrations of deoxycholic acid induce apoptosis in colon cancer cells (30). Nair et al (31) have found a tissue-bound form of lithocholate with a free form in human liver, which can be hydrolytically released using clostridial cholanoylamino acid hydrolase. They have demonstrated a specific conjugation of the ⑀-amino group of a lysine residue to the carboxyl group of a bile acid and investigated the relationship to promotion of carcinogenesis (32).…”
Section: Discussionmentioning
confidence: 99%
“…Low doses of primary bile acids increase the number of aberrant crypt foci in the colon (29); conversely, higher concentrations of deoxycholic acid induce apoptosis in colon cancer cells (30). Nair et al (31) have found a tissue-bound form of lithocholate with a free form in human liver, which can be hydrolytically released using clostridial cholanoylamino acid hydrolase. They have demonstrated a specific conjugation of the ⑀-amino group of a lysine residue to the carboxyl group of a bile acid and investigated the relationship to promotion of carcinogenesis (32).…”
Section: Discussionmentioning
confidence: 99%
“…While they each display an [M -57]+ ion, the ion relative abundances vary and, unlike the carboxylic acid substituents, it is not the dominant ion in the high-mass region of their spectra. N-( 1-Propy1)lithocholylamide (4) has the most pronounced [M -57]+ ( Fig. 7(a), m/z 360).…”
Section: Effect Of Other N-substituents On the Mass Spectra Of Lithocmentioning
confidence: 99%
“…In 1977, lithocholic acid (LCA), a hydrophobic bile acid, was firstly isolated as a tissue-bound form from pathological specimens of human livers by Nair et al, 1,2 and its concentration was reported to be elevated in the livers of rat treated with a carcinogen, methylazoxymethanol. 3 Furthermore, the tissuebound LCA was detected in normal and neoplastic human mammary tissues and in the neoplasms of the uterus, kidney, lung and the colon.…”
Section: Introductionmentioning
confidence: 99%